Evaluation Compliance Storage of Drugs Against Standard Service Pharmacy in Pharmacy In Palembang City - Nia Azzahra; Exta Angelica; Reni Hasdiah (JURNAL LENTERA ILMIAH KESEHATAN, 2026)
Drug storage is an important component of pharmaceutical management because it determines the quality, safety, stability, and effectiveness of medicines before dispensing. This study evaluated drug storage compliance at three community pharmacies in Palembang City against 19 parameters derived from Regulation of the Minister of Health of the Republic of Indonesia Number 73 of 2016. A descriptive observational cross-sectional study was conducted in April 2026. Three pharmacies were purposively selected based on active licensing and operation, the availability of a pharmacist in charge, willingness to provide observational access, and variation in location and service characteristics. Data were collected by one observer through direct observation using a checklist mapped to the 19 regulatory parameters; operationally irrelevant items were coded as not applicable (NA) and excluded from the denominator. Among 18 applicable parameters, compliance was 94.44% (17/18) at Pharmacy A, 88.89% (16/18) at Pharmacy B, and 94.44% (17/18) at Pharmacy C. Non-compliance involved inadequate segregation of near-expiry medicines at Pharmacies A and B, inconsistent FIFO/FEFO implementation at Pharmacy B, and storage not fully arranged by therapeutic class at Pharmacy C. None of the pharmacies stocked vaccines; therefore, the vaccine parameter was classified as NA. These findings indicate that high aggregate scores may conceal specific operational risks. Pharmacies should establish designated near-expiry areas, strengthen visual labeling and stock rotation, and conduct more frequent documented monitoring.